Penerapan Model Concept Teaching Pendekatan Concept Attainment untuk Meningkatkan Pemahaman Konsep Ipa Fisika Siswa Kelas Viii1 Smp Negeri 5 Kendari pada Materi Pokok Usaha dan Energi - La Sahara (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This research aims to describe an increase the activity of learning and concept understanding of physics science by application the concept teaching model to the concept attainment approach on the subject matter work and energy. ÃÂ The research is classroom action research with the subject is grade VIIIF SMPN 5 Kendari which consisting of 33 students. Data obtained from the observation sheet and the concept understanding tests. Technique of data analysis is calculates the average score learning activities, the average value of the concept understanding and determine student learning success each cycle. Results of the research that this approach can increase the activity of student learning and concept understanding of physics science at students. An average score of learning in cycle I of a 2,8 increase to 3,5 on cycle II. The same as,ÃÂ  the average value of concept understanding physics science in cycle I of 66,9 increased to 79,2 on cycle II. The percentage of student learning success is also on the cycle I of 48,5% increase to 87,9% in cycle II, with a value of KKM determinated from school of 70. Thus, the application of the concept attainment approach is one of the right alternative solutions to increase of the students concept understanding of physics science especially on the subject matter work and energy. Therefore, expected that teacher can implemented the concept attainment approach in concept physics that contains the definition of the concept, characteristics, atributtes and relationships between concepts are the students more easily understand the conceptÃÂ  of physics well.